Could saline instillation displace bacteria from the endotracheal tube biofilm to lower airways during suctioning procedure? - CR Franchi, Anália Cristina; Filho, Antônio Pazin; Bottura, Camila; Miranda, Carlos Henrique; Ferreira, Fernanda B; de C Borges, Marcos; de C Santana, Rodrigo; Okino, Valéria T (Critical care (London, England), 2015)
The bacteria observed were: five Gram-positive (Staphylococcus aureus in three, Streptococcus pneumoniae in one and Staphylococcus haemolytics in one) and three Gram-negative (Acinetobacter baumani, Klebsiella pneumoniae, Enterobacter cloacae). Conclusion The use of saline during an endotracheal suctioning procedure can dislocate pathogenic bacteria from the endotracheal tube biofilm to the lower airways, and could increase the risk of VAP.